Comprehensive Treatment Approaches in a Unique Case of Generalized Pustular Psoriasis - Earlia, Nanda; Maulida, Mimi; Badiri, Istanul; Pradistha, Aldilla; Bulqiah, Mikyal; Fajrina, Nur (Indonesian Journal of Case Reports, 2023)
Psoriasis is an immunological inflammatory disease characterized by skin inflammation and epidermal hyperplasia. One type of psoriasis is Generalized Pustular Psoriasis (GPP), which is usually preceded by other diseases. A 56-year-old woman presented to the Department of Dermatology and Venereology with a recent onset of red spots accompanied by pustules distributed across her body. The initial manifestation of these symptoms occurred approximately one month prior, and the condition has progressively worsened over the past three days. Physical examination of dermatological status showed erythematous plaques with smooth, well-defined scales with irregular, round edges, lenticular size, multiple, discrete, and confluent distribution, generalized distribution in the pedis dextra et sinistra, manus dextra et sinistra, and femoral regions. Skin biopsy examination results showed skin tissue with hyperkeratosis, acanthosis, and parakeratosis, with PMN inflammatory cells (Munro's micro abscess). The conclusion of the skin biopsy is pustular psoriasis. The patient was diagnosed with GPP. Patients were given Methotrexate, calcitriol tablets 0.25 mcg twice a day, cetirizine tablets 10 mg twice a day, and topical cream. After one week of treatment, the patient's lesions improved. Treatment continues, and patients are given education to avoid trigger factors such as stress, excessive activity, extreme temperature changes, and focal infections. The management must consider various influencing factors, including genetic factors, skin barriers, predisposing factors, and trigger factors. Prevention is also important. The patient needs to be educated about the details of the disease, how to prevent a recurrence, and treatment when the disease recurs.